Listening Comprehension Difficulties Faced by EFL Students - Hermida, Rita (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2021)
This study analyzes the students difficulties in comprehending listening in English. The study used a quantitative method to investigate the problems faced by students in taking listening comprehension test. The data were collected by distributing the questionnaires and carrying out interview to the students. The study was carried out at an Islamic Boarding School in Aceh Besar District, Aceh Province. The findings showed that the students had limited chance to repeat the words, lack of listening length and speed, lack of contextual, culture and background knowledge, and poor grammar and vocabulary.